Preparation method and application of itaconic acid-based polymer material
By designing and synthesizing macromolecular crosslinking agents and using them for the preparation of acrylic resin adhesives, the problem of aging and falling off under high temperature conditions is solved, and higher bonding and high temperature resistance are achieved.
Patent Information
- Application Number
- CN202411978825.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing acrylic resin adhesives age and fall off under high temperature conditions, resulting in their high temperature resistance being relatively average, which limits their wide application.
By designing and synthesizing macromolecular crosslinking agents, the polymer structure with alternating connection between adamantyl linker and phenylsulfone is used to enhance the stability of the molecular chain of the acrylic resin, and crosslinking it through macromolecular crosslinking agents to form a three-dimensional network structure to improve the bonding performance and high temperature resistance of the material.
It significantly improves the bonding and high-temperature resistance of acrylic resin adhesives, keeping them stable under high temperature conditions and extending their service life.
Smart Images

Figure CN119798520A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a preparation method and application of an itaconic acid-based polymer material. Background Art
[0002] Acrylic resin is a polymer compound, which is polymerized from acrylic acid, methacrylic acid and their derivatives. Acrylic resin has excellent film-forming properties, transparency and adhesion, which makes it widely used in many fields, especially in the adhesive field. Compared with other types of adhesives, acrylic resin adhesives have higher saturation and better antioxidant properties. They are not easy to turn yellow under long-term sunlight exposure. In addition, the glass transition temperature of acrylic resin is low, which makes it have good softness and viscosity, suitable for a variety of printing materials. Therefore, it has played an important role in many products such as pressure-sensitive adhesives, structural adhesives, hot melt adhesives, and occupies an important position.
[0003] However, with the advancement of science and technology and the continuous development of adhesive technology, the application of acrylic resin in the adhesive field will be more extensive and in-depth. Therefore, the research and development of acrylic resin will pay more attention to its high performance and multifunctionality. Among them, the enhancement of bonding performance is the top priority. In addition, in the long-term application process, it is found that the high temperature resistance performance of acrylic resin adhesive is also relatively general. Long-term use in a high temperature environment may cause aging and shedding, which also affects the continued application of acrylic resin adhesive.
[0004] Since acrylic resin is prepared by free radical polymerization of acrylic ester monomers, the adhesive properties and high temperature resistance of acrylic resin can be further improved by improving the synthesis method and adding functional monomers, thereby broadening its application field. Based on this, the present invention provides an itaconic acid-based polymer material, which has good comprehensive properties such as bonding properties and can be directly used as an adhesive. Summary of the invention
[0005] 1. Technical issues to be solved
[0006] In view of the deficiencies in the prior art, the present invention provides a preparation method and application of an itaconic acid-based polymer material.
[0007] (II) Technical solution
[0008] A method for preparing an itaconic acid-based polymer material, wherein the itaconic acid-based polymer material is prepared from the following raw materials in parts by weight:
[0009]
[0010] The preparation method comprises the following steps:
[0011] The first step is to weigh and prepare all the raw materials according to their weight;
[0012] Step 2: Add itaconic acid, methyl acrylate, isooctyl acrylate and butyl methacrylate to the organic solvent, start stirring, and after mixing evenly, raise the temperature to 75-78°C, and then add the initiator to the formed mixed solution. After adding, keep the mixture warm for 1-2 hours to form a prepolymer;
[0013] The third step is to add the macromolecular cross-linking agent into the prepolymer, and then further increase the temperature to 80-83°C. After heat preservation for 8-16 hours, stop heating, cool down and discharge the material to obtain the itaconic acid-based polymer material.
[0014] As a further embodiment of the present invention, the preparation method of the macromolecular cross-linking agent is as follows:
[0015] Add the adamantyl linker and toluene solvent to a reactor filled with nitrogen in sequence. After the addition, start stirring and control the stirring rate to 100-200r / min. After mechanical stirring, add the chain extender to the reactor. After the addition, gradually increase the temperature to 70-80°C, and add the phase transfer catalyst to the reactor. After stirring for 6-9 hours, remove the nitrogen, evaporate and remove the solvent, stop heating, cool and discharge, and the macromolecular cross-linking agent can be obtained.
[0016] As a further embodiment of the present invention, the adamantyl linker is 4,6-bis(1-adamantyl)-1,3-diglycidyl ether benzene.
[0017] As a further embodiment of the present invention, the chain extender is 4,4'-sulfonylbis[2-(2-propenyl)]phenol.
[0018] As a further embodiment of the present invention, the molar ratio of the adamantyl linker to the chain extender is 1.1-1.2:1.
[0019] As a further embodiment of the present invention, the phase transfer catalyst is boron trifluoride ether complex.
[0020] As a further solution of the present invention, the mass of the phase transfer catalyst added is 2-3% of the total mass of the adamantyl linker and the chain extender.
[0021] In the above technical scheme, the adamantyl linker structure contains a terminal epoxy group, which can undergo a ring-opening reaction with the phenolic hydroxyl group in the chain extender structure under the action of a phase transfer catalyst. Since the chain extender structure contains two equivalents of phenolic hydroxyl substituents, the two can undergo continuous ring-opening polymerization to form a polymer macromolecular chain containing an alternating structure. Since the reactant structure contains unsaturated olefinic functional groups, the product structure of the ring-opening polymerization will contain a large number of polymerizable unsaturated olefinic functional groups, which can act as a cross-linking agent, i.e., a macromolecular cross-linking agent, in the free radical polymerization process of the acrylate monomer.
[0022] As a further embodiment of the present invention, the initiator is benzoyl peroxide or dicumyl peroxide.
[0023] As a further embodiment of the present invention, the organic solvent is ethyl acetate or butyl acetate.
[0024] An application of an itaconic acid-based polymer material, wherein the itaconic acid-based polymer material prepared by the above-mentioned preparation method is applied in the field of adhesives.
[0025] (III) Beneficial technical effects
[0026] The present invention designs the acrylic resin molecular chain structure, firstly designs a unique synthetic macromolecular crosslinking agent, the macromolecular crosslinking agent is a macromolecular polymer alternately connected by adamantane and phenylsulfone, the presence of these rigid heterocycles can greatly increase the stability of the acrylic resin molecular chain, so that it can remain stable under high temperature conditions, in addition, after being crosslinked by the macromolecular crosslinking agent, the crosslinking density of the acrylic resin molecular chain is greatly increased, and the linear structure is converted into a three-dimensional network structure, which can have a higher cohesive force on the one hand, improve the bonding performance of the material, and on the other hand, the movement of the acrylic ester molecular chain can be greatly hindered, and the high temperature stability of the material can be improved laterally. In addition, the macromolecular crosslinking agent structure also contains a large number of ether bonds and active hydroxyl substituents generated by the ring-opening reaction, and the selected itaconic acid structure also contains two equivalents of active carboxyl substituents, these groups can produce more hydrogen bond connection sites with the adhered substrate, so that the bonding performance of the material can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0028] Figure 1 This is the FT-IR graph of the macromolecular cross-linking agent. DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0030] Preparation Example 1
[0031] Preparation of macromolecular cross-linking agent:
[0032] To a reactor filled with nitrogen, 0.2 g of 4,6-bis(1-adamantyl)-1,3-diglycidyl ether benzene and toluene solvent were added in sequence. After the addition, stirring was started and the stirring rate was controlled to be 200 r / min. After mechanical stirring, 0.12 g of 4,4'-sulfonylbis[2-(2-propenyl)]phenol was added to the reactor. After the addition, the temperature was gradually increased to 75°C, and 0.008 g of boron trifluoride ether complex was added to the reactor. After stirring for 8 hours, the nitrogen was removed, the solvent was evaporated, the heating was stopped, the temperature was lowered and the material was discharged, and the macromolecular crosslinking agent was obtained.
[0033] Figure 1 This is the infrared analysis test (FT-IR) diagram of the macromolecular cross-linking agent, where 3401cm -1 The characteristic absorption peak at 3098 cm is the characteristic absorption peak of hydroxyl generated by the ring-opening addition reaction. -1 and 3087cm -1 The characteristic absorption peak at 3031cm is the characteristic absorption peak of carbon and hydrogen of the benzene ring skeleton. -1 The characteristic absorption peak at 1060cm is the characteristic absorption peak of carbon-hydrogen on the unsaturated carbon-carbon double bond. -1 The characteristic absorption peak appearing at is the characteristic absorption peak of the ether bond produced by the ring-opening reaction.
[0034] Example 1
[0035] An itaconic acid-based polymer material is prepared from the following raw materials in parts by weight:
[0036]
[0037] The preparation method of the itaconic acid-based polymer material comprises the following steps:
[0038] The first step is to weigh and prepare all the raw materials according to their weight;
[0039] Step 2: Add itaconic acid, methyl acrylate, isooctyl acrylate and butyl methacrylate to ethyl acetate, start stirring, and after mixing evenly, raise the temperature to 75°C, and then add benzoyl peroxide to the resulting mixed solution. After adding, heat it for 2 hours to form a prepolymer.
[0040] The third step is to add the macromolecular cross-linking agent into the prepolymer, and then further increase the temperature to 80°C. After heat preservation for 16 hours, stop heating, cool down and discharge the material to obtain the itaconic acid-based polymer material.
[0041] The macromolecular cross-linking agent is the macromolecular cross-linking agent prepared in Preparation Example 1, and the same applies hereinafter.
[0042] Example 2
[0043] An itaconic acid-based polymer material is prepared from the following raw materials in parts by weight:
[0044]
[0045] The preparation method of the itaconic acid-based polymer material comprises the following steps:
[0046] The first step is to weigh and prepare all the raw materials according to their weight;
[0047] Step 2: Add itaconic acid, methyl acrylate, isooctyl acrylate and butyl methacrylate to butyl acetate, start stirring, and after mixing evenly, raise the temperature to 76°C, and then add dicumyl peroxide to the resulting mixed solution. After adding, heat-preserve for 2 hours to form a prepolymer;
[0048] The third step is to add the macromolecular cross-linking agent into the prepolymer, and then further increase the temperature to 82°C. After heat preservation for 12 hours, stop heating, cool down and discharge the material to obtain the itaconic acid-based polymer material.
[0049] Example 3
[0050] An itaconic acid-based polymer material is prepared from the following raw materials in parts by weight:
[0051]
[0052]
[0053] The preparation method of the itaconic acid-based polymer material comprises the following steps:
[0054] The first step is to weigh and prepare all the raw materials according to their weight;
[0055] Step 2: Add itaconic acid, methyl acrylate, isooctyl acrylate and butyl methacrylate to butyl acetate, start stirring, and after mixing evenly, raise the temperature to 78°C, and then add dicumyl peroxide to the resulting mixed solution. After adding, heat preservation for 1 hour to form a prepolymer;
[0056] The third step is to add the macromolecular cross-linking agent into the prepolymer, and then further increase the temperature to 83°C. After heat preservation for 8 hours, stop heating, cool down and discharge the material to obtain the itaconic acid-based polymer material.
[0057] Comparative Example 1
[0058] An itaconic acid-based polymer material is prepared from the following raw materials in parts by weight:
[0059]
[0060] The preparation method of the itaconic acid-based polymer material comprises the following steps:
[0061] The first step is to weigh and prepare all the raw materials according to their weight;
[0062] Step 2: Add itaconic acid, methyl acrylate, isooctyl acrylate and butyl methacrylate to butyl acetate, start stirring, and after mixing evenly, raise the temperature to 76°C, and then add dicumyl peroxide to the resulting mixed solution. After adding, heat-preserve for 2 hours to form a prepolymer;
[0063] The third step is to add 4,4'-sulfonylbis[2-(2-propenyl)]phenol to the prepolymer, and then further increase the temperature to 82°C. After heat preservation for 12 hours, stop heating, cool down and discharge the material to obtain the itaconic acid-based polymer material.
[0064] Comparative Example 2
[0065] An itaconic acid-based polymer material is prepared from the following raw materials in parts by weight:
[0066]
[0067] The preparation method of the itaconic acid-based polymer material comprises the following steps:
[0068] The first step is to weigh and prepare all the raw materials according to their weight;
[0069] The second step is to add itaconic acid, methyl acrylate, isooctyl acrylate and butyl methacrylate into butyl acetate, start stirring, and after mixing evenly, raise the temperature to 76°C, and then add diisopropylbenzene peroxide to the formed mixed solution. After the addition is complete, keep the mixture warm for 2 hours, and then further raise the temperature to 82°C. After keeping the mixture warm for 12 hours, stop heating, cool and discharge the material to obtain the itaconic acid-based polymer material.
[0070] Test Case
[0071] The polymer materials in the examples and comparative examples were uniformly coated on the surface of the PET substrate, and the coating amount was controlled to be 10 g / cm 2 After the hike is completed, it is placed in an oven at 100°C for 30 minutes of curing, taken out, and then covered with a layer of release film on the coated surface, and then aged in a temperature environment of 60°C for 12 hours, taken out, and made into samples for testing. The test results are recorded in the following table:
[0072] Table 1 - Test results
[0073]
[0074]
[0075] Note: The test method refers to the standard GB / T 2791-1995. First, perform routine tests on the samples to obtain the initial values. After the test, place the samples of the same batch in an oven at 150°C for 24 hours and then test them to obtain the heat treatment values. By comparing the drop in peel strength before and after heat treatment, the high temperature resistance of the samples can be judged. Generally speaking, the smaller the drop, the stronger the high temperature resistance, and vice versa.
[0076] The analysis and test results show that the polymer material prepared by cross-linking the acrylate monomer with the macromolecular cross-linking agent prepared in Preparation Example 1 shows significantly better bonding performance and high temperature resistance than the polymer material prepared without adding the macromolecular cross-linking agent.
[0077] After replacing the macromolecular cross-linking agent with 4,4'-sulfonylbis[2-(2-propenyl)]phenol, the resulting acrylic resin molecular chain does not contain adamantane heterocyclic structure and the cross-linking density is relatively low, so both the bonding performance and high temperature resistance performance show a significant decrease.
[0078] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
[0079] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an itaconic acid-based polymer material, characterized in that: The itaconic acid-based polymer material is made of the following raw materials in parts by weight: The preparation method comprises the following steps: The first step is to weigh and prepare all the raw materials according to their weight; Step 2: Add itaconic acid, methyl acrylate, isooctyl acrylate and butyl methacrylate to the organic solvent, start stirring, and after mixing evenly, raise the temperature to 75-78°C, and then add the initiator to the formed mixed solution. After adding, keep the mixture warm for 1-2 hours to form a prepolymer; The third step is to add the macromolecular cross-linking agent into the prepolymer, and then further increase the temperature to 80-83°C. After heat preservation for 8-16 hours, stop heating, cool down and discharge the material to obtain the itaconic acid-based polymer material.
2. The method for preparing an itaconic acid-based polymer material according to claim 1, characterized in that: The preparation method of the macromolecular cross-linking agent is as follows: Add the adamantyl linker and toluene solvent to a reactor filled with nitrogen in sequence. After the addition, start stirring and control the stirring rate to 100-200r / min. After mechanical stirring, add the chain extender to the reactor. After the addition, gradually increase the temperature to 70-80°C, and add the phase transfer catalyst to the reactor. After stirring for 6-9 hours, remove the nitrogen, evaporate and remove the solvent, stop heating, cool and discharge, and the macromolecular cross-linking agent can be obtained.
3. The method for preparing an itaconic acid-based polymer material according to claim 2, characterized in that: The adamantyl linker is 4,6-bis(1-adamantyl)-1,3-diglycidyl ether benzene.
4. The method for preparing an itaconic acid-based polymer material according to claim 2, characterized in that: The chain extender is 4,4'-sulfonylbis[2-(2-propenyl)]phenol.
5. The method for preparing an itaconic acid-based polymer material according to claim 2, characterized in that: The molar ratio of the adamantyl linker to the chain extender is 1.1-1.2:
1.
6. The method for preparing an itaconic acid-based polymer material according to claim 2, characterized in that: The phase transfer catalyst is boron trifluoride ether complex.
7. The method for preparing an itaconic acid-based polymer material according to claim 2, characterized in that: The added mass of the phase transfer catalyst is 2-3% of the total mass of the adamantyl linker and the chain extender.
8. The method for preparing an itaconic acid-based polymer material according to claim 1, characterized in that: The initiator is benzoyl peroxide or dicumyl peroxide.
9. The method for preparing an itaconic acid-based polymer material according to claim 1, characterized in that: The organic solvent is ethyl acetate or butyl acetate.
10. An application of an itaconic acid-based polymer material, characterized in that: The itaconic acid-based polymer material prepared by the method for preparing an itaconic acid-based polymer material as described in any one of claims 1 to 9 is applied in the adhesive field.
Citation Information
Patent Citations
Adamantane derivative, method for producing the same, and resin composition containing adamantane derivative
CN101547885A
Adamantane-containing photosensitive resin for black matrix photoresist, preparation method of photosensitive resin, resin composition of photosensitive resin and application method of photosensitive resin
CN114380937A
Adamantane compound and method for producing the same
JP2012153605A